High‐angular resolution diffusion imaging tractography of cerebellar pathways from newborns to young adults. Issue 1 (29th October 2016) - Re, Thomas J.; Levman, Jacob; Lim, Ashley R.; Righini, Andrea; Grant, Patricia Ellen; Takahashi, Emi
Abstract: Introduction: Many neurologic and psychiatric disorders are thought to be due to, or result in, developmental errors in neuronal cerebellar connectivity. In this connectivity analysis, we studied the developmental time‐course of cerebellar peduncle pathways in pediatric and young adult subjects. Methods: A cohort of 80 subjects, newborns to young adults, was studied on a 3T MR system with 30 diffusion‐weighted measurements with high‐angular resolution diffusion imaging (HARDI) tractography. Results: Qualitative and quantitative results were analyzed for age‐based variation. In subjects of all ages, the superior cerebellar peduncle pathway (SCP) and two distinct subpathways of the middle cerebellar peduncle (MCP), as described in previous ex vivo studies, were identified in vivo with this technique: pathways between the rostral pons and inferior‐lateral cerebellum (MCP cog ), associated predominantly with higher cognitive function, and pathways between the caudal pons and superior‐medial cerebellum (MCP mot ), associated predominantly with motor function. Discussion: Our findings showed that the inferior cerebellar peduncle pathway (ICP), involved primarily in proprioception and balance appears to have a later onset followed by more rapid development than that exhibited in other tracts. We hope that this study may provide an initial point of reference for future studies of normal and pathologic development of cerebellar connectivity. Abstract : This work demonstrates the usefulness of HARDI tractography for studying the normal development of the cerebellar peduncle pathways in a pediatric population. We showed that it is possible to distinguish in vivo two subpathways of the middle cerebellar peduncle (MCP), the motor component (MCPmot) and the higher cognitive function component (MCPcog) at all ages even in the premature newborn.